Metastatic Pulmonary Calcification An Uncommon Clinical Condition in End-Stage Renal Disease - Gaurav Patel; Andre Yepes-Hurtado; Isham Huizar (Southwest Respiratory and Critical Care Chronicles, 2013)
Patients with end-stage renal diseases have frequent pulmonary complicationsrelated to fluid overload, infection, and associated cardiovascular diseases. We reporta 73-year-old man with renal failure on peritoneal dialysis who had elevated serum calcium,phosphorous, and parathyroid hormone levels. He had progressive dyspnea andan abnormal chest x-ray. A high resolution computed tomography scan revealed calcifiednodules, large cavities with heavy calcification in the upper zones, calcifications inthe tracheobronchial tree, and calcified vessels. This patient had metastatic pulmonarycalcification and possibly dystrophic calcification due to renal failure which probablycontributed to his pulmonary symptoms.